2018
DOI: 10.1007/s00345-018-2397-1
|View full text |Cite
|
Sign up to set email alerts
|

An increased body mass index is associated with a worse prognosis in patients administered BCG immunotherapy for T1 bladder cancer

Abstract: The BMI could have a relevant role in the clinical management of T1G3 NMIBC, if associated with bladder cancer recurrence and progression. In particular, this anthropometric factor should be taken into account at initial diagnosis and in therapeutic strategy decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 26 publications
3
87
1
1
Order By: Relevance
“…This was confirmed by the fact that a sensitivity analysis with additional adjustment for smoking status did not change our risk estimates (data not shown). Also, no associations were found in the subgroup of patients initially treated with adjuvant immunotherapy (S5 Table), in contrast to results of Kluth et al [19] and Ferro et al [39]. Our results are in line with those of Wyszynski et al [20], who also found that associations for BMI did not differ by immunotherapy treatment status.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This was confirmed by the fact that a sensitivity analysis with additional adjustment for smoking status did not change our risk estimates (data not shown). Also, no associations were found in the subgroup of patients initially treated with adjuvant immunotherapy (S5 Table), in contrast to results of Kluth et al [19] and Ferro et al [39]. Our results are in line with those of Wyszynski et al [20], who also found that associations for BMI did not differ by immunotherapy treatment status.…”
Section: Discussionsupporting
confidence: 87%
“…Here, statistically significant associations with recurrence (HR; 2.66, 95% CI: 2.13-3.32) and progression (HR: 1.49, 95% CI: 1.00-2.21) were shown when comparing obesity with no obesity [19]. In a recent study by Ferro et al in 1155 T1G3 NMIBC patients treated with maintenance Bacillus Calmette-Guerin (BCG), obesity versus normal weight at diagnosis was associated with an increased risk of recurrence (HR: 5.33; 95% CI: 4.16-6.83) and progression (HR:2.51, 95% CI: 1.76-3.57) as well, with similar but slightly lower risk estimates for overweight [39]. None of these three studies adjusted for smoking status.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, Koebnick et al 12 claimed that obesity increased the risk of bladder cancer and Ferro et al 27 revealed that BMI plays a role in the recurrence and progression of non-muscle-invasive bladder cancer. In the Asian population, a recent study 28 showed that the incidence of bladder cancer was higher in the overweight and obese population.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies have assessed the association between body mass index (BMI) and prognosis [7,24,25,30,34,39,59,[65][66][67][68][69][70][71][72][73][74][75]. One study assessed BMI at diagnosis, [24] 13 studies assessed BMI at time of treatment (e.g., transurethral resection of bladder tumor (TURBT), radical cystectomy), [25,30,34,39,59,[65][66][67][68][69][70][71][72] and three studies did not report timing of BMI measurement [73][74][75].…”
Section: Body Mass Indexmentioning
confidence: 99%